A2.29 Immature dendritic cells are potent osteoclasts precursors in ra and are targeted by ra-specific antibodies. (24th February 2016) - Krishnamurthy, A; Sun, M; Rethi, B; Joshua, V; Wähämaa, H; Tarasova, N; Amara, K; Malmström, V; Ytterberg, J; Catrina, AI
Abstract : Background and purpose: We have recently shown that the immature dendritic cells (iDC) developing in dense cultures in presence of high lactic acid levels can efficiently differentiate into osteoclasts (OC). We aimed to investigate influence of Anti-citrullinated protein antibodies (ACPA) on iDC differentiation to OC in rheumatoid arthritis (RA). Methods: CD14 + monocytes from PB of ACPA+ RA patients and healthy individuals were first used to generate iDC and MΦ and these cells were then differentiated to OC with RANKL and M-CSF. Mass spectrometry analysis was performed on different stages of differentiation of iDC and MΦ derived OC. ACPA positive and negative polyclonal IgGs were isolated from synovial fluid (SF, n = 26) and peripheral blood (PB, n = 38) samples of RA patients and the effects of these antibodies was tested in OC cultures. Cytokines were measured by CBA in cultures supernatants. Immunoflourescence was done on OCs with monoclonal ACPAs derived from single SF derived B cells. The effect of IL-8 and PAD inhibition was tested on OC differentiation. Results: Principal component analysis confirmed distinct proteomics profiles in sparse or dense DC cultures and in MΦ but both DC and MΦ precursors differentiated into OC with similar protein composition. Citrullinated-actin was identified during iDC-OC maturation and citrullinated-vimentin in matured OC. With immunofluorescent staining we demonstrated the presence of citrullinated proteins on the surface of both iDC precursors and iDC-derived mature OCs. PAD2 and PAD4 showed faint staining in CD14 monocytes with increased staining intensity in both iDC precursors and more mature OCs. Polyclonal ACPAs enhanced osteoclastogenesis and bone resorption from iDC (fold increase 1.6 ± 0.2 for OC number and 2.0 ± 0.3 for bone resorption area). Similar effect was observed when the iDC were derived from ACPA+ RA patients (fold increase of 2.3 ± 0.9 for OC number and 2.6 ± 0.1 for bone resorption area). The importance of citrullination and PAD enzymes for ACPA mediated iDC transdifferentiation to OC was confirmed by a dose-dependent inhibition of OC differentiation using the PAD inhibitor Cl-Amidine. Increased osteoclastogenesis was associated with significantly higher levels of IL-8 levels in cultures supernatants (fold increase of 2.4 ± 0.5). Conclusion: iDC can efficiently transdifferentiate in to OC in RA and this process is enhanced by ACPA.